Ergodic properties of non-homogeneous Markov chains on ordered Banach spaces - Mukhamedov, Farrukh (2014)
In the present work, we define such an ergodicity coefficient of a positive mapping defined on ordered Banach space with a base (OBSB), and study its properties. In terms of this coefficient we prove the equivalence uniform and weak ergodicities of homogeneous Markov chains.